2019
DOI: 10.1182/bloodadvances.2018024182
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of NAMPT by KPT-9274 in acute myeloid leukemia

Abstract: Key Points• KPT-9274, via its protein target NAMPT, diminishes NAD 1 levels and cellular respiration, leading to cell death.• Orally bioavailable KPT-9274 exhibits targetspecific activity in cell lines and patientderived xenograft models of AML. Treatment options for acute myeloid leukemia (AML) remain extremely limited and associated with significant toxicity. Nicotinamide phosphoribosyltransferase (NAMPT) is involved in the generation of NAD 1 and a potential therapeutic target in AML. We evaluated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
5
35
0
Order By: Relevance
“…Earlier studies from our group and others have demonstrated remarkable anti-tumor activity of KPT-9274 in solid (breast, colon, and kidney) and hematologic (NHL, CLL, and MM) tumor xenograft models [25][26][27][28]. Our group has also demonstrated the activity of KPT-9274 in PDAC xenograft in vivo [29].…”
Section: Kpt-9274 Shows Single Agent Anti-tumor Activity In Pnetsupporting
confidence: 64%
“…Earlier studies from our group and others have demonstrated remarkable anti-tumor activity of KPT-9274 in solid (breast, colon, and kidney) and hematologic (NHL, CLL, and MM) tumor xenograft models [25][26][27][28]. Our group has also demonstrated the activity of KPT-9274 in PDAC xenograft in vivo [29].…”
Section: Kpt-9274 Shows Single Agent Anti-tumor Activity In Pnetsupporting
confidence: 64%
“…MGG119, MGG152, BT142 primary glioblastoma cell lines; HT1080, 30T and SW1353 chondrosarcoma cell lines; SNU484, SNU668, SNU1750, MKN1 and Hs746T gastric cancer cell lines which have mutations in IDH1 [7][8][9], were sensitive to NAMPT inhibition. NAMPT inhibitors not only have shown promising effect as single-agent therapy, but were also found to sensitize other modalities of cancer treatment in both in vitro and in vivo experiments [45,[55][56][57], as shown in Tables 2 and 3. As preclinical studies with NAMPT showed encouraging results [73][74][75], the clinical efficacy and safety of NAMPT inhibitors has been tested in cancer patients.…”
Section: Therapeutic Role Of Nampt In Cancermentioning
confidence: 99%
“…In addition to Ewing sarcoma, recent insights have revealed that other pediatric cancers may also be susceptible to NAMPT inhibition. Preclinical models of pediatric hematologic malignancies, including B-and T-cell leukemias (112,113), and AML (114,115) underwent growth inhibition upon treatment with single agent NAMPT inhibitors. Models of pediatric HGG, including diffuse pontine gliomas (DIPG) were also sensitive to inhibition of NAMPT, which may be mediated by genetic silencing of compensatory enzymes (116).…”
Section: Nicotinamide Adenine Dinucleotide (Nad + ) Metabolismmentioning
confidence: 99%